Traditions matrimoniales dans la région de Rabat-Salé-Zemmour-Zaer au Maroc - Hinde Hami; Abdelmajid Soulaymani; Abdelrhani Mokhtari (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The practice of consanguineous marriage has been widespread for hundreds of years, and is still very common, especially among various Middle Eastern, Asian and African populations where 20 to 50% + of marriages are consanguineous. The analysis of a sample of 270 married women selected randomly in the Maternity Service of the Hospital Souissi of Rabat (2004-2005) was subjected to a prospective study to determine the frequency of consanguineous marriages in the region of Rabat-Salé-Zemmour-Zaer in Morocco. The results indicate that 20% of marriages were consanguineous (95% CI 12.29-28.01%), of which over 70% were between first cousins.